Insulin resistance by homeostatic model assessment in patients of polycystic ovarian syndrome - Jadhav, Aishwarya S.; Dabade, Rajiv T. (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2025)
Polycystic ovarian syndrome (PCOS) is one of the common endocrine disorders of reproductive age and affects approximately 6-16% of general population. Considering high incidence (70-95%) of insulin resistance in women with high BMI, 30-75% of population is found to have insulin resistance inspite of being lean. So, it is worth proving insulin resistance irrespective of BMI. Of amongst different tests to diagnose insulin resistance, homeostatic model assessment of insulin resistance (HOMA-IR) has been proved to be useful as a screening test for insulin resistance. This is a retrospective observational study of 4 months from April 2022 to July 2022 and included 18 patients diagnosed with PCOS. We studied their BMI, fasting glucose, fasting insulin and HOMA-IR. Out of total patients screened, the prevalence of insulin resistance was 72.22% as calculated by HOMA-IR test. No prevalence of HOMA-IR was observed in underweight cases. Out of normal weight cases, 83.33% cases were found to have Insulin resistance. Of the overweight and obese cases, 100% were found to have insulin resistance. Majority of women with PCOS have insulin resistance and consequent hyperinsulinemia. Insulin resistance is directly proportional to weight gain in PCOS patients. Lifestyle modification and administration of insulin sensitizers like Metformin is useful in reducing insulin resistance in overweight and obese patients. In patients with normal BMI who prove to have insulin resistance with raised HOMA-IR test are also benefited from medical therapy.